Effect of specific mineral supplementation on the blood profile of dairy cattle of Himachal Pradesh - VERMA, M S; KUMAR, R; SHARMA, K B (The Indian Journal of Animal Reproduction, 2023)
After initial assessment of mineral status of the animals, the selected animals were supplemented with specifically formulated mineral mixture for 30 days. Resu(ts indicated si ni_ficant in_crease in average concentrations of Ca p Na and Cl whereas Mg and K levels increased non-significantly in the blood of the animals after specifid rriineral supplementation. The overall mean plasma Cu and Zn concentrations increased significantly from 0:59 ± 0.03 to 0.70 ± 0.04 μg/!’11 and from 0.81 ± 0.04 μg/ml to_0.90 ± 0.0 μg/ml respec_tivefi after mineral supplementation. Numerically the number of anoestrous animals declined after mineral supplementation but it was non-significant.